(untitled) (Web of Teachers: Inderscience Research, 2025)
This article analyzes the scientific and theoretical foundations of teaching information technology and the effectiveness of pedagogical methods. In the study, new training modules were developed based on the theory of cognitive load and interactive teaching methods, and their impact on the educational process was assessed through experimental tests. Local and foreign experience was studied, and the role of digital technologies in increasing the effectiveness of education was shown. The research results serve as a scientific and practical basis for the introduction of innovative pedagogical approaches into the education system of Uzbekistan and the improvement of the quality of education. The prospects for the integration of artificial intelligence and virtual reality technologies into education in the future were discussed.